2015
DOI: 10.1111/apt.13374
|View full text |Cite
|
Sign up to set email alerts
|

Systemic review: the pathogenesis and pharmacological treatment of hiccups

Abstract: SUMMARY BackgroundHiccups are familiar to everyone, but remain poorly understood. Acute hiccups can often be terminated by physical manoeuvres. In contrast, persistent and intractable hiccups that continue for days or months are rare, but can be distressing and difficult to treat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
205
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(283 citation statements)
references
References 37 publications
(47 reference statements)
3
205
0
20
Order By: Relevance
“…Physiological studies have demonstrated a mechanism by which these manoeuvres improve hiccups, with the frequency of hiccups decreasing as arterial PCO 2 rises. 6 In the case of persistent hiccups, the following drugs are used: haloperidol 2-5 mg/24 hr, metoclopramide 10 mg, baclofen 7 5 mg/8 hr, phenytoin, valproic acid, carbamazepine, gabapentin, amitriptyline, and amantadine. 8 Chlorpromazine 25-50 mg intramuscularly or intravenously is effective in up to 80% of cases.…”
Section: Managementmentioning
confidence: 99%
“…Physiological studies have demonstrated a mechanism by which these manoeuvres improve hiccups, with the frequency of hiccups decreasing as arterial PCO 2 rises. 6 In the case of persistent hiccups, the following drugs are used: haloperidol 2-5 mg/24 hr, metoclopramide 10 mg, baclofen 7 5 mg/8 hr, phenytoin, valproic acid, carbamazepine, gabapentin, amitriptyline, and amantadine. 8 Chlorpromazine 25-50 mg intramuscularly or intravenously is effective in up to 80% of cases.…”
Section: Managementmentioning
confidence: 99%
“…1 We found no randomized controlled trials to compare the effectiveness of drug therapies for persistent or intractable hiccups; however, chlorpromazine has been effective in clinical practice and is the only medication approved by the US Food and Drug Administration for hiccups. Several alternative medications have been reportedly effective in the medical literature, including gabapentin.…”
Section: Go To Sectionmentioning
confidence: 99%
“…All are proposed to act on the GABAergic or dopaminergic neurons of the medulla. 1 The patient was admitted to the hospital neurology service and a course of chlorpromazine was administered. His hiccups, nausea, and vomiting resolved in less than 24 hours.…”
Section: Supplemental Data At Neurologyorgmentioning
confidence: 99%
“…The center of the arc is thought to be located between cervical 3 and 5, whereas the efferent part consisted of phrenic nerve, accessory respiratory muscles, the glottis, and autonomic processes with medullary reticular formation and hypothalamus. However the exact pathophysiology is unclear 3,4 . The clinical manifestation may be transient and can be defined as hiccups lasting 48 hours or less, or persistent in cases of hiccups lasting longer than 48 hours, or intractable when it lasts more than a month.…”
Section: Introductionmentioning
confidence: 99%